Crinoid-associated pontoniine shrimps of the genus Laomenes Clark, 1919 (Decapoda, Caridea, Palaemonidae) from PANGLAO 2004 and KUMEJIMA 2009 Expeditions, with description of two new species - Marin, Ivan; Chan, Tin-Yam; Okuno, Junji (Zootaxa, 2012)
Four species of the crinoid-associated pontoniine shrimps of the “Laomenes amboinensis (De Man, 1888)” species groupwere collected in the Philippines PANGLAO 2004 and Ryukyu KUMEJIMA 2009 Expeditions. Two of them, L.pestrushka n. sp. from the Ryukyus and L. gyrophthalmus n. sp. from the Philippines, are new to science. The two others, L. cornutus (Borradaile, 1915) and L. holthuisi Marin & Okuno, 2010, are rarely collected species.